A systematic review on COVID‐19 vaccination and cosmetic filler reactions: A focus on case studies and original articles. (31st May 2022) - Kalantari, Yasamin; Aryanian, Zeinab; Mirahmadi, Seyed‐Mohamad‐Sadegh; Alilou, Sanam; Hatami, Parvaneh; Goodarzi, Azadeh
Abstract: Background: Tissue fillers are among the most popular cosmetic procedures performed and notably, cases of filler reactions after COVID‐19 vaccination have been reported. Objective: The objective was to determine the characteristics of patients with filler reaction after COVID‐19 vaccination and address several considerations that have to be taken into practice. Methods: A PRISMA compliant systematic search was conducted in Scopus, Web of Science, and PubMed/MEDLINE databases for articles published from inception up to October 21, 2021. Results: Out of 106 initially retrieved articles, four of them were included in our study, and a total number of 13 cases were analyzed. In this study, we found that all of the patients who developed delayed‐type reaction (DTR) following COVID‐19 vaccination were middle‐aged women without any known history of allergy to foods or drugs. All patients had a history of hyaluronic acid (HA) filler injection in their head and neck and demonstrated symptoms particularly swelling, from <1 day up to 10 days after the first or second doses of vaccines. Lisinopril, hyaluronidase, and corticosteroids seemed to have good results in management. Conclusion: Although rare, DTR to fillers after COVID‐19 vaccination can happen. Physicians should be aware of the pathogenesis and management of this phenomenon.